Perancangan Website Profil Program Studi Menggunakan Content Management System Wordpress - khaliq, abdul (Jurnal Nasional Teknologi Komputer, 2023)
This article discusses designing a study program profile website using the WordPress Content Management System (CMS). Higher education has a need to present relevant and up-to-date information to prospective students, students, lecturers, and the general public. A study program profile website can be an effective tool to meet these needs. The design method used in this study involves the stages of needs analysis, interface design, selecting the appropriate WordPress theme, developing special features relevant to the study program, and testing functionality. Using the WordPress CMS as a content management platform makes it easy to manage and update content independently without requiring advanced programming skills. The result of this research is a responsive, attractive, and easy to navigate study program profile website. The features implemented include information about study programs, curriculum, lecturers, facilities, and the latest news. In addition, it is equipped with a search feature to make it easier for users to find the specific information they want. Implementing the WordPress CMS as a content management platform provides time and cost efficiency benefits in managing websites. In addition, the flexibility and ease of adding or changing content ensures that the information presented is always up-to-date relevant. In conclusion, designing a study program profile website using the WordPress CMS is an effective solution for presenting up-to-date and relevant information to stakeholders in the academic environment. This research contributes to the field of information technology, especially in the use of CMS platforms for efficient content management in the context of higher education.